Serum lipid, lipoprotein and oxidatively modified low density lipoprotein levels in active or inactive patients with behçet's disease - Fuat Cimen; Sembol Turkmen Yildirmak; Andac Ergen; Mustafa Cakmak; Serkan Dogan; Necati Yenice; Funda Sezgin (Wolters Kluwer Medknow Publications, 2012)
Aim: To determine serum lipid, lipoproteins and oxidized low density lipoprotein (oxLDL) levels in Behçet's disease (BD) and to evaluate the relationship of these parameters with the clinical activity of the disease. Materials and Methods: Sixty-two patients (25 active, 37 inactive) and -26 healthy controls were included in the study. We measured serum oxLDL levels using the enzyme-linked immunosorbent assay method, and serum total cholesterol (TC), triglyceride (TG) and high density lipoprotein-cholesterol (HDL-C) levels by spectrophotometric method. Results: Serum TG (108±70 mg/dL and 79±40 mg/dL, respectively; P<0.05), LDL-C (124±35 mg/dL and 108±26 mg/dL, respectively; P<0.05) and oxLDL (65±19 U/L and 53±10 U/L, respectively; P<0.01) levels were significantly higher in patients than in controls, but HDL-C levels were significantly lower in patients than in controls (39±11 mg/dL and 50±13 mg/dL, respectively; P<0.05). The levels of oxLDL in patients were found to correlate with those of TC and LDL-C. Neither the lipid parameters nor the oxLDL levels in the patients with active disease (n=25) were different than those in the patients who were in inactive stage (n=37). Serum levels of oxLDL in the patients with active and inactive disease were significantly higher than those in controls (66±19 U/L, 65±19 U/L, and 53±10 U/L, respectively; P<0.05). Conclusions: We conclude that the increase of TG, LDL-C and oxLDL levels and the decrease of HDL-levels may indicate that there is a tendency to atherothrombotic process in patients with BD. Inflammation and immunologic reactions in BD may be caused by a response to elevated oxLDL. TG, LDL-C and oxLDL are not useful markers for the severity of the disease activity.